Inovasi Pemerintahan Daerah Dalam Perubahan Perilaku Hidup Sehat: Studi Program Motor Balap di UPT Puskesmas Paringin Selatan Kabupaten Balangan - Ferdi Fajar Padilah; Fitriyani Fitriyani; Sipa Tania; Fadjar Tri Sakti (STISIP Margarana, 2026)
This study discusses a regional government innovation aimed at encouraging changes in healthy lifestyle behavior through the Motor Balap Program implemented at the Paringin Selatan Community Health Center in Balangan Regency. The main problem addressed in this research is the increasing risk of noncommunicable diseases, which is associated with low levels of physical activity, unhealthy dietary patterns, and limited health education among rural communities. The purpose of this study is to provide a comprehensive description of the program’s concept, implementation, and its impact on improving healthy lifestyle behaviors within the community. The method used in this research is a descriptive qualitative approach by collecting data through literature review and document analysis related to the implementation of the program. The results show that the Motor Balap Program is able to enhance community knowledge, participation, and motivation in practicing healthy lifestyle behaviors through guidance from motivators, regular educational activities, and the use of a digital information-based application. The conclusion of this study emphasizes that Motor Balap is an effective innovation in strengthening healthy lifestyle practices, supporting efforts to prevent noncommunicable diseases, and having strong potential to be replicated as a community-based health policy model in other regions.